Effectiveness of Indoor Residual Spraying as A Method of Controlling Dengue Fever in Communities: A systematic review - Titik Anggraeni; Sarwoko Sarwoko; Sutanta Sutanta; Bambang Sudono Dwi Saputro; Hana Rosiana Ulfah; Habid Al Hasbi; Vina Asna Afifah; Ilma Widiya Sari; Emy Kurniawati; Ahmad Syamsul Bahri; Herbasuki Herbasuki (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Dengue remains a significant public health issue in the Western Pacific Region. In the absence of a vaccine, vector control is the mainstay for dengue prevention and control. This study aimed to explore the effectiveness of Indoor Residual Spraying as A Method of Controlling Dengue Fever in Communities. Subjects and Method: A systematic review was conducted by searching articles from PubMed, ResearchGate, Science Direct, Google Scholar, and EBSCO is an article published from 2013 to 2023. The keywords were “dengue hemorrhagic fever” OR “DHF” AND “community” OR “family” AND “disaster” AND “IRS” OR “indoor residual spraying”. The inclusion criteria were a Cross-sectional study. The articles were selected by PRISMA flow diagram method. Results: A total of 9 studies were included in this review. All of the studies stated that IRS can have both an immediate and sustained effect on reducing adult and immature A. aegypti populations and should be considered as an adult mosquito control strategy by dengue vector control programs also IRS led to 86-96% reduction in dengue cases in sprayed premises, compared to unsprayed controls. Conclusion: IRS significantly reduces the malaria burden in high-transmission settings. Keywords: dengue hemorrhagic fever, DHF, family, community. Correspondence: Titik Anggraeni. School of Health Sciences Estu Utomo Boyolali, Central Java, Indonesia. Jl. Tentara Pelajar 7, Mudal, Boyolali, Central Java, Indonesia. Email: titik.anggraeni146@gmail.com. Mobile: +62 858-6729-2673.